Comparative genotoxic and developmental effects of bisphenol analogs on human lymphocytes and Lymnaea stagnalis - Alessandro Nota; Thomas Hesselberg; Alessia Pappalardo; Alfredo Santovito (Environmental Toxicology and Pharmacology, 2026)

New records of Priacanthus arenatus in the Mediterranean Sea: morphological and molecular evidence with biogeographic insights - Luca Castriota; Manuela Falautano; Alessandro Nota; Francesco Tiralongo (Frontiers in Marine Science, 2026)
We report two new records of the Atlantic bigeye, Priacanthus arenatus Cuvier, 1829, from Italian waters (Ionian Sea and Strait of Sicily), confirmed through morphological and molecular analyses. The species has previously been reported in the Mediterranean only twice, in the Gulf of Cagliari and the Strait of Messina. Morphometric and meristic data were compared with literature values, and phylogenetic analyses based on COI sequences confirmed species identity and suggested affinity with an eastern Atlantic haplotype. Ecological implications and taxonomic considerations are discussed.

New records of introduced species in the Mediterranean Sea (December 2025) - MICHEL BARICHE; SHAHENAZ M. ABD ELLAH; OKAN AKYOL; EMAN SALEM ALFERGANI; ANDREA ALVITO; FIRAS ALSHAWY; IZDIHAR ALI AMMAR; ÉRICA CAROLINE BECKER; GIAMBATTISTA BELLO; DAMLA BETON; SENEM ÇAĞLAR; GIOVANNI CANDUCI; et al. (Mediterranean Marine Science, 2025)
New records of introduced species in the Mediterranean Sea (December 2025)

In vitro genomic damage caused by glyphosate and its metabolite AMPA - Alfredo Santovito; Alessandro Nota; Paolo Pastorino; Claudio Gendusa; Enrico Mirone; Marino Prearo; Dasa Schleicherová (Chemosphere, 2024)

Chronicles of Kyphosus in the Mediterranean Sea: new records and complete mitogenomes support the scenario of one expanding fish species - Alessandro Nota; Francesco Tiralongo; Alfredo Santovito; Antonio Torroni; Anna Olivieri (Frontiers in Marine Science, 2024)
The Mediterranean Sea is a biodiversity hotspot, being home to a vast array of marine species. Furthermore, seawater warming is facilitating the arrival and spread of new thermophilic species, posing a severe threat to biodiversity. Among the species currently extending their range and increasing in abundance in Mediterranean waters, sea chubs (genus Kyphosus ) are one of the most enigmatic. One challenge arises from the high phenotypic similarity between the two congeneric species documented in the basin: Kyphosus vaigiensis and Kyphosus sectatrix . Their resemblance has often led to identification challenges, resulting in incorrect or omitted species-level classifications. Therefore, despite the growing presence of these fish in the Mediterranean, it remains unclear whether only one or both species are experiencing a demographic increase and range extension. To date, there have been 26 reports of Kyphosus individuals in the Mediterranean Sea, documented in 24 separate papers. Here, we reviewed the history of the genus in the basin and provided 13 new records of these fish from multiple localities along Mediterranean coasts. In addition, we sequenced the entire mitogenomes of two specimens, assessed their phylogenetic relationships with published Kyphosus mitochondrial DNAs from around the world, and conducted detailed morphological and meristic analyses on one of them, allowing us to provide accurate species-level identifications. Our results indicate that K. vaigiensis is the species currently expanding its range in the Mediterranean Sea, while K. sectatrix is still very rare and only sporadically reported. Notably, our mitogenome data indicate that Mediterranean K. vaigiensis individuals most likely came from Atlantic waters, while there is no evidence to support an entrance through the Red Sea or any other anthropogenic vector. Finally, the potential ecological and fishing impacts associated with the proliferation of these fish in the region are discussed.

Genotoxicological and physiological effects of glyphosate and its metabolite, aminomethylphosphonic acid, on the freshwater invertebrate Lymnaea stagnalis - Dáša Schleicherová; Paolo Pastorino; Alessia Pappalardo; Alessandro Nota; Claudio Gendusa; Enrico Mirone; Marino Prearo; Alfredo Santovito (Aquatic Toxicology, 2024)

Adaptation to bioinvasions: When does it occur? - Alessandro Nota; Sandro Bertolino; Francesco Tiralongo; Alfredo Santovito (Global Change Biology, 2024)
The presence of alien species represents a major cause of habitat degradation and biodiversity loss worldwide, constituting a critical environmental challenge of our time. Despite sometimes experiencing reduced propagule pressure, leading to a reduced genetic diversity and an increased chance of inbreeding depression, alien invaders are often able to thrive in the habitats of introduction, giving rise to the so‐called “genetic paradox” of biological invasions. The adaptation of alien species to the new habitats is therefore a complex aspect of biological invasions, encompassing genetic, epigenetic, and ecological processes. Albeit numerous studies and reviews investigated the mechanistic foundation of the invaders' success, and aimed to solve the genetic paradox, still remains a crucial oversight regarding the temporal context in which adaptation takes place. Given the profound knowledge and management implications, this neglected aspect of invasion biology should receive more attention when examining invaders' ability to thrive in the habitats of introduction. Here, we discuss the adaptation mechanisms exhibited by alien species with the purpose of highlighting the timing of their occurrence during the invasion process. We analyze each stage of the invasion separately, providing evidence that adaptation mechanisms play a role in all of them. However, these mechanisms vary across the different stages of invasion, and are also influenced by other factors, such as the transport speed, the reproduction type of the invader, and the presence of human interventions. Finally, we provide insights into the implications for management, and identify knowledge gaps, suggesting avenues for future research that can shed light on species adaptability. This, in turn, will contribute to a more comprehensive understanding of biological invasions.

Purebred dogs show higher levels of genomic damage compared to mixed breed dogs - Alfredo Santovito; Martina Saracco; Manuel Scarfo’; Alessandro Nota; Sandro Bertolino (Mammalian Genome, 2024)
Inbreeding is a common phenomenon in small, fragmented or isolated populations, typical conditions of many threatened species. In the present paper, we used a new non-invasive approach based on the buccal micronucleus assay to evaluate the possible relationships between inbreeding and genomic damage using the dog as model species. In particular, we assessed the frequencies of micronuclei and other nuclear aberrations in a group of purebred dogs ( n = 77), comparing the obtained data with those from a control group represented by mixed breed dogs ( n = 75). We found a significant increase of micronuclei, nuclear buds and total nuclear aberrations frequencies in purebred dogs compared to mixed-bred dogs. The absence of significant differences in the frequency of micronuclei and other nuclear aberrations amongst different breeds reinforces the hypothesis that the observed increased genomic damage amongst purebred dogs may not be due to a different genomic instability typical of a particular breed, but to inbreeding itself. This hypothesis is further confirmed by the fact that other endogen confounding factors, such as sex, age and weight, do not contribute significantly to the increase of genomic damage observed amongst purebred dogs. In conclusion, results presented in this study showed that, in purebred dogs, inbreeding may increase the levels of genomic damage. Considering that genomic damage is associated with increased physiological problems affecting animal health, the results we obtained may represent a stimulus to discourage the use of intensive inbreeding practices in captive populations and to reduce the fragmentation of wild populations.

Strengthening global-change science by integrating aeDNA with paleoecoinformatics - John W. Williams; Trisha L. Spanbauer; Peter D. Heintzman; Jessica Blois; Eric Capo; Simon J. Goring; Marie-Eve Monchamp; Laura Parducci; Jordan M. Von Eggers; Inger Greve Alsos; Chris Bowler; Marco J.L. Coolen; et al. (Trends in Ecology & Evolution, 2023)